2021
DOI: 10.4102/jef.v14i1.633
|View full text |Cite
|
Sign up to set email alerts
|

The impact of employee remuneration inequalities on employee productivity in the South African workplace

Abstract: Orientation: This article is part of an ongoing research project on various aspects of employee productivity in the South African workplace.Research purpose: The aim of this article is to determine firm-based employee productivity impacts as a result of employee remuneration inequalities (excess-remuneration and under-remuneration) in the South African workplace.Motivation for the study: The study focuses on understanding the impact and magnitude of employee remuneration inequalities on employee productivity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Autonomy relates to providing employees the freedom to decide on how and when they want to execute tasks. Working in the hospitality industry often involves a hectic work schedule and long hours (Van Zyl, 2011). Also, teamwork is often expected in performing tasks (like preparing meals, planning events and setting up venues), which implies that employees need to cultivate good interpersonal and communication skills.…”
Section: Outline Of the Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Autonomy relates to providing employees the freedom to decide on how and when they want to execute tasks. Working in the hospitality industry often involves a hectic work schedule and long hours (Van Zyl, 2011). Also, teamwork is often expected in performing tasks (like preparing meals, planning events and setting up venues), which implies that employees need to cultivate good interpersonal and communication skills.…”
Section: Outline Of the Resultsmentioning
confidence: 99%
“…Ruiz and Davis (2017) confirmed that employee turnover is a pressing challenge for the hospitality industry. Some of the reasons for the high employee turnover in the hospitality industry are long hours, challenges in work-life balance and poor compensation (Van Zyl, 2011). Mbane (2017) found a strong correlation between fair compensation and employee retention in the hospitality industry.…”
Section: The Job Characteristics Model and Millennial Hospitality Emp...mentioning
confidence: 99%